(untitled) (Fiep Bulletin - online, 2017)
The elderly population in Brazil increased in recent years, which is attributed to increased life expectancy,so physical activity is an important means of prevention and promotion of health of the elderly through its numerous benefits. It isestimated that the participation of the elderly in regular exercise programs may influence the aging process, improving the qualityand life expectancy, greater personal independence and guarantee a beneficial effect on the control, treatment and prevention ofdiseases. This research demonstrates and puts information describing the resistance training for older people. The basis of thisresearch was the study of books, specialized articles and electronic data, which made it possible to access and manipulaterelevant information to analyze the importance effect of resistance training in promoting the health of the elderly. Training usingthe system sets and repetitions, and repetitions are characterized by repetitive exercises without rest, and the series all theserepetitions. Overloading has used its value between 50-80% of 1RM with series ranging from 2 to 3 per year and the number ofrepetitions between 6 and 15, using time rest around 2 to 3 minutes. The frequency depends on how the training plan, but it wouldaverage 4 to 5 times a week. Thus it concluded that properly prescribed and directed regular exercise play an important role inprevention, conservation and recovery of functional capacity of the elderly. Thus by applying the resistance training programscorrectly the desired benefits can be achieved for the health of the elderly, helping directly and positively in the performance ofactivities of daily living, favoring the improvement of much of the physical variables that are affected by the aging process .